Socio-Cultural Intervention As Disaster Mitigation In Indonesia - Musrayani Usman; Mario Mario; Sopian Tamrin; Riri Amandaria (Universitas of Muhammadiyah Makassar, 2022)
The Republic of Indonesia needs a mitigation system due to considering how vulnerable the archipelago to disasters. Compiled from The National Disaster Management Authority (BNPB) data in 2021, Indonesia will have to deal with 1,441 natural disasters in the period from January to June. This situation gets worse because until now Covid-19 is still high in various corners of the country. Various efforts in the context of handling the disasters have encountered obstacles that could slow down the recovery of the community. Indonesia's disaster management is still absent in playing its role. Therefore, it is necessary to optimize various aspects, including social and cultural capital as an important force. Natural disaster mitigation needs to be done by basing the wealth of cultural heritage, traditions and local wisdom. In addition to saving budget, mitigation models that use social power like this are more responsive so that prevention and recovery can be carried out earlier. This study aims to analyze and identify socio- cultural intervention as a disaster mitigation. This study uses a qualitative method with an explanatory descriptive approach. The data collection was done by using observation, interview, and documentation techniques. The result of this study indicates that disaster management in Indonesia is still spontaneous and does not optimize mitigation interventions in social and cultural aspects such as social networks and local wisdom values. The socio-cultural intervention system is very realistic because local wisdom exists in every community in the archipelago. This is good for the community to respond to disaster problems.